2020
DOI: 10.1038/s41467-020-15753-4
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise internal potential jumps caused by multiple-domain polarization flips in metal/ferroelectric/metal/paraelectric/metal stack

Abstract: Negative capacitance (NC) effects in ferroelectric/paraelectric (FE/PE) stacks have been recently discussed intensively in terms of the steep subthreshold swing (SS) in field-effect transistors (FETs). It is, however, still disputable to stabilize quasi-static-NC effects. In this work, stepwise internal potential jumps in a metal/FE/metal/PE/metal system observed near the coercive voltage of the FE layer are reported through carefully designed DC measurements. The relationship of the internal potential jumps w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…One can see that internal voltage amplifications (δ V int /δ V G > 1) can be observed in both sweeping directions in the I D – V G scan. Note that although direct measurement methods of the internal gate voltage V int during the I D – V G scan exist, previous studies , have pointed out that a voltage measurement system with input impedance much larger than the leakage resistances of the capacitors is required to accurately measure these voltages, which is not available in our measurement system. Therefore, we have adopted the strategy of indirectly extracting V int from the measured I D .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One can see that internal voltage amplifications (δ V int /δ V G > 1) can be observed in both sweeping directions in the I D – V G scan. Note that although direct measurement methods of the internal gate voltage V int during the I D – V G scan exist, previous studies , have pointed out that a voltage measurement system with input impedance much larger than the leakage resistances of the capacitors is required to accurately measure these voltages, which is not available in our measurement system. Therefore, we have adopted the strategy of indirectly extracting V int from the measured I D .…”
Section: Resultsmentioning
confidence: 99%
“…Different from the original proposal, alternative mechanisms for the observed steep slope switching have been proposed and the validity of a stabilizing negative capacitance (NC) region of FE materials has been challenged [11][12][13] . For example, some papers relate the observed steep switching to transient effects such as internal potential jumps 14,15 or differential voltage amplification caused by polarization switching of FE material [16][17][18][19][20][21][22] , instead of a quasi-static NC effect represented as the "S"-shaped curve in the polarization-electric field (P-E) relation of FE materials 1,23,24 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Most recently, Li et al reported a stepwise internal potentialjump phenomenon in measuring the DC voltage applied to the capacitor in a series connection with a metal/PZT/metal FE capacitor [94]. They claimed that the accuracy of their measurement setup is optimized by increasing the equivalent resistance of the voltmeter (Fig.…”
Section: Possible Origins Of Steep Ssmentioning
confidence: 99%